Екологічна освіта в Польщі на початку ХХІ століття (англійською мовою) - Волтер, Едита (Studies in Comparative Education, 2013)
У статті представлено проблему екологічної освіти в постмодерній культурі другої половини ХХ – поч. ХХІ ст. Екологічну освіту розглянуто як ідею збереження природи і практичну діяльність у глобальному масштабі. Автор звертає увагу на особливості екологічної освіти в Польщі після реформи 1999 року. Структура статті базується на класифікуванні проблем, перед якими постає екологічна освіта у світі в цілому і в Польщ, зокрема. Статья посвящена проблеме экологического образования в постмодерной культуре второй половины ХХ – нач. ХХІ века. Экологическое образование представлено через идею сохранения природы и практическую деятельность в глобальном масштабе. Автор обращает внимание на особенности экологического образования в Польше после реформы 1999 г. The article presents ecological education issue in the general post-modern culture trend from the second half of the 20th and at the beginning of the 21st century Ecological education is an implication of the idea of nature conservation and the practical activities in this field on a global scale. The aim of this article is to present the ecological education in the Polish Republic after the 1999 education reform. The article’s structure is based on the problem differentiation concerning international activities in the field of nature conservation and ecological education in the Polish education system.